Land Use Change Modeling to Support the Management Plan of Protected FMU Unit II FMU Region XV Kabanjahe - Fauziah Sahara; Anita Zaitunah; Bejo Slamet (Journal of Sylva Indonesiana, 2026)
Deforestation results in environmental degradation, so it is necessary to conduct a study to determine land use changes that occur and predict land changes with appropriate directions to support the Protected FMU Unit II FMU Region XV Kabanjahe management plan. This study aims to analyze changes and predictions of land use in 2013-2033, factors that influence land use change, and formulate directions for land use plans in Protected FMU Unit II FMU Region XV Kabanjahe. This research uses a Geographic Information System approach with the Artificial Neural Network (ANN) method prediction model. Factors driving land use change as model inputs consist of distance to road, distance to permit, distance to settlement, distance to river, elevation, geology, soil type, and slope. The results showed that there has been a decrease in dryland forest by 6,957 ha in the 2013-2018 period, and the driving factor that has the highest degree of relationship based on the results of the correlation test is the distance to the road, which is 0.2444. The land use change prediction model has an accuracy of 89.42% based on Kappa Index Agreement (KIA). The direction of the land use plan in Protected FMU Unit II FMU Region XV Kabanjahe in 2033 consists of Protected Forest Area which has the largest area, namely 64,678 ha, Production Forest covering 7,077 ha, and Limited Production Forest covering 9,278 ha.